1974
DOI: 10.1111/j.1399-6576.1974.tb00847.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acid‐Base Changes on Central Nervous System Toxicity of Local Anaesthetic Agents II

Abstract: This study is a detailed analysis of data obtained from 127 experiments on 90 paralysed and ventilated cats regarding the CNS toxicity of nine local anaesthetic agents as evidenced by seizure activity on the EEG. It is shown that an increase in Pco2 or aH+ caused increased CNS toxicity, i.e., smaller i.v. doses were required to elicit seizure activity, and that the underlying metabolic acid‐base state can considerably modify this, a metabolic alkalosis decreasing toxicity, and vice‐versa. The probable mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…It has been shown that increased plasma PaCO 2 and consequent changes in the acid-base state caused an exponential increase in the central toxicity of many local anesthetic agents. 15,16 In this same way Ryan et al 33 affirmed that hypercarbia decreases the convulsive threshold of local anesthetic agents. It is also important to note the cerebral vasculature response to PaCO 2 as a factor affecting toxicity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been shown that increased plasma PaCO 2 and consequent changes in the acid-base state caused an exponential increase in the central toxicity of many local anesthetic agents. 15,16 In this same way Ryan et al 33 affirmed that hypercarbia decreases the convulsive threshold of local anesthetic agents. It is also important to note the cerebral vasculature response to PaCO 2 as a factor affecting toxicity.…”
Section: Discussionmentioning
confidence: 72%
“…10,14 Studies in cats have shown that the acid-base state is an important factor, in that acidosis increased, while alkalosis reduced, anesthetic toxicity. 15,16 An increase in the levels of PaCO 2 can worsen the convulsive threshold, and a decrease in PaCO 2 levels tends to have the opposite effect. 17,18 The duration of seizure activity is related to the local anesthetic blood level and is directly related to the arterial PaCO 2 level.…”
mentioning
confidence: 99%
“…Maintenance of a patent airway and respiratory support is essential. Studies using cats, dogs, and sheep have shown that LA intoxication is more severe in the presence of acidosis (respiratory or metabolic), hypercarbia, and hypoxia [31][32][33][34]. Thus, avoidance of hypoventilation causing respiratory acidosis and hypoperfusion causing metabolic acidosis is key.…”
Section: Discussionmentioning
confidence: 98%
“…Continuous or frequent intermittent monitoring of systemic blood pressure and ECG is also prudent if present cardiopulmonary arrest should be treated with standard cardiopulmonary resuscitation, which historically has been relatively refractory to treatment [26,38]. The most effective positive ionotrope, vasopressor, or antiarrhythmic remains unknown, although correction of hypotension and arrhythmias leading to hypoperfusion appears to be essential [16,[31][32][33]. Kasten et al described effective cardiovascular resuscitation after bupivicaine overdose in anesthetized dogs using open-chest cardiac massage, bretylium, atropine, epinephrine, and intravenous crystalloid fluids [27].…”
Section: Discussionmentioning
confidence: 99%
“…14 Although severe cardiotoxicity was rarely seen in our study, there might be a risk for cardiac arrhythmias, which are a characteristic manifestation of local anaesthetic agent toxicity. As acidosis is known to increase local anaesthetic toxicity 28 it seems plausible that conditions such as seizures and respiratory depression, which are observed in tolperisone overdose and are associated with acidosis, will further exacerbate tolperisone toxicity.…”
Section: Discussionmentioning
confidence: 99%